William W. answered • 02/21/19

Math and science made easy - learn from a retired engineer

The quadratic equation is (for ax^{2} + bx + c = 0), x = (-b __+__ sqrt(b2 - 4ac))/2a

In this case a = 1, b = 6, and c = -7

Plug them in and simplify. You should get x = 1 and x = -7 but of course, you need to show all the steps.

If you need help, let me know

William W.

x = (-b +/- sqrt(b2 - 4ac))/2a and a = 1, b = 6, and c = -7 so: Step 1: x = (-6 +/- sqrt(6^2 - 4(1)(-7)))/2(1) Step 2: x = (-6 +/- sqrt(36 - -28))/2 Step 3: x = (-6 +/- sqrt(36 +28))/2 Step 4: x = (-6 +/- sqrt(64))/2 Step 5: x = (-6 +/- 8)/2 Breaking the +/- into two pieces: Step 6: x = (-6 + 8)/2 and x = (-6 - 8)/2 Step 7: x = 2/2 = 1 and x = -14/2 = -702/21/19

Michael C.

I don't think I did it right can I see it step by step?02/21/19